The Influence of Student Learning Motivation and Family Environment on Student Learning Outcomes - Rahmad; Keysia Vectrina Zahra; Vivid Vidyasari; Asri Karolina (STAI YAPTIP Simpang Empat Pasaman Barat Indonesia in collaboration with International Islamic Studies Development and Research Center (IISDRC), 2025)
This study evaluates the influence of learning motivation and family environment on the learning outcomes of fourth-grade students at MI Al-Ishlah Palembang. This study used quantitative methods. The analysis found that learning motivation has a significant positive influence with a contribution of 64.7% to learning outcomes. The family environment also has a significant positive influence, explaining 49.7% of the variation in learning outcomes. Regression analysis showed that the combination of these two factors explained 65.7% of the variation in learning outcomes. These findings emphasize the importance of motivation and family support in improving student academic achievement.